Efeitos do trabalho em turnos rotativos nas condições de saúde e aspectos psicossociais em trabalhadores de uma empresa de papel - Abreu, Graciela Junqueira de (2011)
Background: The existence of firms of national and international produce in a continuous and uninterrupted, and so organize the work period, dividing it in turn is increasing. There are several types of shift work, both shifts with fixed schedules, such as rotating shifts, and the choice of one of the types of companies takes place according to the satisfaction of its demand and not according to the psychophysiological characteristics of workers. Several studies analyze the effects of different types of turns and try to list all the consequences for workers, which guided the preparation of this work. This research aims to study the profile of workers at a paper company in the field who work rotating shifts, evaluating the influence of these shifts in terms of physical and psychosocial health, to obtain responses that may lead to prevention of problems. Methods: The research it is a cross sectional study was conducted in a company in the city of Três Lagoas / MS, in which 104 rotating shift workers were interviewed and answered three self-applied questionnaires, among which are the Quality Index the Pittsburgh Sleep Scale, Epworth sleepiness Scale and stress at Work, which seek to assess the perception of workers about their quality of sleep and the presence of excessive daytime sleepiness in workers, as well as the stress level. Data were analyzed using descriptive statistics and chi-square test for a significance level of 5%. Results: The questionnaires were correlated and the results show that there was no association of stress with sleep quality (P = 0.288) and daytime sleepiness (P = 0.355) and the mean scores of stress, sleep quality and sleepiness diurnal shown that individuals are well. Conclusions: No association between stress, sleep quality and daytime sleepiness, this suggests that the shift rotation may exert less deleterious effects on workers.